Doping of Fullerene‐Like MoS2 Nanoparticles with Minute Amounts of Niobium. (11th December 2017) - Rosentsveig, Rita; Yadgarov, Lena; (Isai) Feldman, Yishay; Shilstein, Sana; Popovitz‐Biro, Ronit; Visic, Bojana; Sedova, Anastasiya; Cohen, Sidney R.; Li, Yuanyuan; Frenkel, Anatoly I.; Tenne, Reshef
Abstract: Inorganic fullerene‐like closed‐cage nanoparticles of MoS2 and WS2 (IF‐MoS2 ; IF‐WS2 ), are synthesized in substantial amounts and their properties are widely studied. Their superior tribological properties led to large scale commercial applications as solid lubricants in numerous products and technologies. Doping of these nanoparticles can be used to tune their physical properties. In the current work, niobium (Nb) doping of the nanoparticles is accomplished to an unprecedented low level (≤0.1 at%), which allows controlling the work function and the band gap. The Nb contributes a positive charge, which partially compensates the negative surface charge induced by the intrinsic defects (sulfur vacancies). The energy diagram and position of the Fermi level on the nanoparticles surface is determined by Kelvin probe microscopy and optical measurements. Some potential applications of these nanoparticles are briefly discussed. Abstract : In situ doping of MoS2 nanoparticles with fullerene‐like structure (IF‐MoS2 ) with tiny amounts (<0.1 at%) of niobium atoms is reported. The doping is shown to partially cancel the negative surface charge induced by the intrinsic defects and lower the Fermi level of the nanoparticles.